Reflection of the kazakh-russian-english trilingualism in oil ergonyms (Eurasian Journal of Philology Science and Education, 2025)
A study of the language situation in the oil industry shows that currently the oil industry of Kazakhstan is served by three languages and therefore it is trilingual (Kazakh, Russian, English). The article provides a linguistic analysis of ergonyms for oil companies. The methods of forming ergonyms for the oil industry are the same as in common vocabulary. The main ones are ergonyms-phrases, ergonyms-compound words and abbreviations. A large group of names is formed through compounding. Toponyms act as mandatory elements in the formation of oil ergonyms - compound words.The main components of the ergonyms are the words «мұнай», «нефть» and «oil», which are not translated, although they have equivalent equivalents in all three languages under study. Interpenetrating into languages, they become an integral part of the vocabulary of the Kazakh, Russian and English languages. When transferring names from one language to another and a third, transliteration occurs.The material for the study of ergonyms was selected from trilingual nominations of oil companies operating in five western regions of Kazakhstan. The practical significance of the study lies in the fact that this material can be used as an additional source of information in the study of ergonyms and is considered as one of the stages on the path to further comparative research.Keywords: ergonym, toponymy, oil industry, trilingualism, abbreviation.